A STUDY OF DIAGNOSTIC APPLICABILITY OF NS1 AND IGM ELISA IN DENGUE FEVER IN A TERTIARY CARE HOSPITAL, VISAKHAPATNAM - KAUSAR, SHAIK TASLEEM; VANI, THAMMINA MEHER SRI SAI SUDHA; KUMARI, POOSAPATI RATNA (International Journal of Current Pharmaceutical Research, 2024)
Objective: The present study aims at diagnostic applicability of NS1 antigen and IgM antibody detection in Dengue fever by ELISA method. Methods: A prospective study for a period of one year from June 2023 to June 2024 was carried out on 13531 blood samples received from inpatients aged between 03 to 45 y admitted with a history of acute phase of fever>99.5°F, myalgia, arthralgia for more than 3 days duration. All the samples received were processed in Virology Research and Diagnostic Laboratory, Department of Microbiology, Andhra Medical College, King George Hospital, Visakhapatnam. Blood samples received were centrifuged @3000 rpm for 10 min, serum seperated and those single sera samples were tested for both NS1 antigen and IgM antibody by ELISA methodology. Cutoff values were calculated according to kit insert instructions. Biochemical laboratory parameters and prognostic markers like platelet count was also taken into consideration in the study. Results: Positivity in this study was 16.3% (2212 of 13531). OD reading more than cutoff value was interpreted as positive or reactive. Detection range varied from 100% by NS1 Ag and 88% by IgM Ab ELISA, thus inferring sensitivity and specificity of respective procedures. Conclusion: Epidemic episodes of dengue fever are frequently reported during monsoon. Hence, combination of NS1 and IgM on single serum samples can improve the diagnostic accuracy during acute phase of dengue fever and help in initiation of therapy and epidemic control to reduce morbidity and mortality.